A new technique to find the facial nerve and recess by using the short process of the incus and the spine of Henle as landmarks: incus-spine angle. - Yilmazer, Rasim; Baskadem Yilmazer, Ayca; Hoffer, Michael E.; Eshraghi, Adrien A.; Telischi, Fred F.; Angeli, Simon I. (Acta Oto-Laryngologica, 2018)
Background: Precise techniques to find the facial nerve (FN) and recess are lacking. Objectives: We aimed to define incus-spine and incus-FN angles which can be used to localize the FN and recess during mastoidectomy. Material and methods: Thirty adult cadaveric temporal bones were studied. Canal-wall up mastoidectomy with a facial recess approach was performed. The temporal bones and microscope were positioned differently to change the visual angle. The following distances were measured: (1) Short process of the incus (SPI)-FN; (2) Body of the incus-FN. Photographs were taken. Three lines were drawn on the photographs between the SPI, FN, and the spine of Henle. The angles were created and measured. Results: Three of the temporal bones were excluded due to the absence of the spine of Henle and two of them due to the displacement of the SPI. The mean of the incus-spine angle in 25 temporal bones was 90.12° and the mean of the Incus-FN angle was 135.96°. The mean distances of the SPI-FN and body of incus-FN were 4.85 and 9.26 mm, respectively. Conclusions and significance: The incus-spine and the incus-FN angles along with the distances can help localize the FN and recess.